A SOCIO-PRAGMATICS OF GRATITUDE STRATEGIES ON NCT’S BEAUTIFUL MUSIC VIDEO COMMENTS - Kuny Salma Aziza; Elisa Nurul Laili (JURNAL ILMIAH NUSANTARA, 2024)
Gratitude strategies is speech acts of communicative acts frequently and abundantly utilized in human interactions. This study aims to find out the types of thank you strategies and the differences between men and women in expressing them written by fans in the Youtube comment section. Data were collected based on fan comments that corresponded to the types of gratitude strategies. The data source comes from one of NCT's music videos entitled Beautiful. Following a descriptive qualitative research design, the researcher identified different types of gratitude strategies and the differences between men and women in expressing them. Researchers also found some differences between men and women in expressing gratitude strategies. Based on the research conducted, there are eight types of gratitude strategies that are thanking, positive feelings, others, attention getter. While the other four types of gratitude strategies were not found in the study that are apology, repayment, recognition of impotition, appreciation. In this study, only four types were found that were relevant to the data taken. from several types of gratitude strategies, each type has several sub-categories. The findings of this study are that women tend to be more expressive than men. The conclusion is that thanking and positive feelings are most often used by fans.